Pelanggaran Kode Etik Profesi Advokat Dalam Ruang Sidang Melalui Peristiwa Pemukulan Hakim oleh Desrizal Chaniago - Pranitiaz, Laras Medina; Lewoleba, Kayus Kayowuan (Media Hukum Indonesia (MHI), 2025)
As a basic guideline, the code of ethics of the advocate profession regulates the behavior and integrity of advocates, especially when carrying out their duties in the courtroom. Advocates have an important role in upholding justice, so they are required to uphold professional ethics in order to maintain the authority of the judiciary. However, in reality, violations of the code of ethics continue to occur, as seen in the incident of the beating of a judge by advocate Desrizal Chaniago which has drawn public attention and tarnished the image of the judicial world. This study aims to examine the provisions of the code of ethics of the advocate profession that regulate the behavior of advocates in the courtroom, as well as to analyze the mechanism for enforcing the code of ethics against violations committed by advocates, focusing on the case of the beating of a judge by Desrizal. This study uses a normative juridical method with a statutory approach and case studies. The results of the study show that Law Number 18 of 2003 concerning Advocates and the Indonesian Advocate Code of Ethics stipulate strict regulations on the behavior of advocates in the courtroom. Desrizal's actions in committing violence against a judge are subject to criminal penalties under Article 212 Jo. Article 351 paragraph (1) of the Criminal Code and sentenced to six months in prison.